Circulating desmosine as a biomarker of azithromycin treatment response: a post hoc analysis of the COLUMBUS randomised controlled trial. Issue 4 (12th November 2018) - Chalmers, James D.; Djamin, Remco S.; Schouten, Marjolijn; Keir, Holly R.; Tan, Brandon; Aerts, Joachim G.J.V.; Huang, Jeffrey T-J.; van der Eerden, Menno
Elastin degradation in the lung, leading to emphysema, and elastin degradation in blood vessels, leading to atherosclerosis, are key mechanisms in the development and progression of chronic obstructive pulmonary disease (COPD) [1]. Elastin degradation can be measured in blood through quantification of desmosine and its isomer iso-demosine, which are released specifically through cleavage of mature elastin [2]. Severe COPD is frequently associated with chronic neutrophil-mediated inflammation and airway microbial dysbiosis [3]. Neutrophils release harmful proteases through the processes of degranulation and neutrophil extracellular trap formation that degrade extracellular matrix, including elastin, leading to disease progression [3, 4]. Circulating desmosine is not reduced by treatment with azithromycin in COPD but elevated desmosine may identify a patient group with a greater treatment response http://ow.ly/vN6N30mhBA1